Efeito da adubação nitrogenada e da cobertura morta sobre os teores de N, P, K, Ca e Mg nas folhas de três cultivares de alho - Ferreira de Novais , Roberto; Alves de Menezes Sobrinho , João; Lopes dos Santos , Hélio; Aguiar Sans, Luiz Marcelo (Revista Ceres, 2025)
The objective of this experiment was to study the effect of three levels of amonium sulfate (0, 500 and 1000 kg/ha) on the growth of three garlic cultivars ("Barbado", "Amarante" and "Branco") when growtn with and without a mulch. For evaluating this effect, foliar analysis were conducted at different stages of the life cycle.